Chemical and Mechanical Characterisation of Clay Soil Stabilised with Steel Slag and Calcium Carbide Waste - Ogundare, Damilola Ayodele; Adeleke, Oyetunde Oluwafemi; Akinbuluma, Ayodeji Theophilus (Civil and Sustainable Urban Engineering, 2024)
Problematic subgrade soil such as clay is expansive by nature and is challenging to work with during pavement construction. In an effort to combat this issue and lower the rate of pavement failure on highway construction projects, cementitious industrial waste materials should be used. This study thus examined the influence of steel slag (SS) and calcium carbide waste (CCW) as stabilisers for clay soil. Chemical and mineralogical analyses of clay soil, SS and CCW were assessed while the stabilised soil were subjugated to Atterberg limit, compaction and california bearing ratio (CBR) tests. The existence of calcium oxide, iron oxide and calcium hydroxide in both the chemical and mineralogical constituents of SS and CCW indicate that they are binding materials which notably influences hardness and contributes more to the strength of the clay soil. With varied amounts of the additives (SS and CCR), the clay soil's liquid limit and plasticity index dropped from 54.0% and 13.8% to 43.5% and 9.2%, respectively. This significantly lowers the clay soil’s swell potential, increases its resilience, and decreases its infiltration capacity. The compaction characteristics revealed that SS and CCW enhanced the compactness of the clay soil signifying enhancement of the soil compaction properties. The CBR value of all the stabilised clay soils improve significantly with 40%SS + 60%CCW acquiring the maximum CBR of 17.3% and 29.0% compared with clay soil having CBR of 4.7% and 6.9% in soaked and unsoaked states respectively.